Emotions and consumer behaviour: A review and research agenda - Sharma, Kirti; Trott, Sangeeta; Sahadev, Sunil; Singh, Ramendra (International journal of consumer studies, 2023)
Consumers' emotions play a salient role in consumers' buying process, their consumption behaviours, and their engagement with product/service offerings, owing to which, it has gained much attention in recent years as an area of inquiry. However, literature in this field/subject is theoretically fragmented. Therefore, to enhance the conceptual understanding, this study synthesizes extant literature, using a hybrid review approach. Herein, we attempt to integrate bibliometric analysis, along with the theories, contexts, characteristics, and methodology framework, while consolidating and classifying the domain knowledge, trends, and progress/citation analysis using the bibliometric approach. In the process, we reviewed 384 conceptual and empirical articles, published during the period 1967–2021. The idea was to identify key theories, constructs, research contexts, and methods, based on which, we propose a few potential research areas. Based on our thorough analysis, these areas include (1) consumer co‐creation, (2) consumer engagement, (3) service employee interactions, (4) consumer decision making, and (5) consumption experience.